Environmental Toxicology / Resource and Environmental Science Series - Duffus John H; Edward Arnold (1980)
In this book the author uses an interdisciplinary approach to the analysis of environmental effects of toxic substances by first dealing with the assessment of toxicity, then describing the metabolism of toxicants by animals, plants and micro-organisms and discussing the present knowledge of toxicants of current concern. Preface, Assessment of Toxicity, Metabolism of Toxic Substances by Animals, Metabolism of Toxic Substances by Plants, Toxic Substances Released into the Environment by Micro-Organisms, Pesticides and Herbicides, Toxic Metals, Atmospheric Toxicants, Petroleum and Radionuclides, Assessment of Environmental Risk, Appendices, Bibliography, Index.